The teaching of the slovak language in schools with hungarian as the language of instruction in Slovakia: general overview - Vančo Ildikó („RIK-U” Kft., 2018)
Abstract. The paper examines the characteristics of the teaching of the Slovak language in schools with Hungarian as the language of instruction in Slovakia, analyzing the factors that affect the teaching process and discussing the legal framework of education in Slovakia. It also looks at the teaching of Slovak as a foreign language and outlines the context of teaching Slovak as a state language, comparing the two in detail. An analysis of the place of the Slovak language among the school subjects is also provided, together with an outline of the national school curriculum of the teaching of Slovak language and Slovak Literature, as it is regulated by law in Slovakia, at the various educational levels.
https://kmf.uz.ua/wp-content/uploads/2018/11/Multicult-Diversity_Book-of-Abstracts_23-10-2018.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00006453
Keywords: slovak language; Slovakia